1999
DOI: 10.1001/archpsyc.56.11.993
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Prenatal and Childhood Infections and the Risk of Schizophrenia

Abstract: Our findings do not support the hypothesis that schizophrenia is associated with prenatal exposure to common infections or influenza. However, they are compatible with the hypothesis that environmental exposure, perhaps to common infections in childhood, may be a risk factor, although other explanations are also possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…A larger study by Adams et al, 8 which included the birth cohort studied by Barr et al, found no such association. Takei et al 39 found an increased risk for subjects exposed 4 months prior to birth (RR = 1.12, 95% CI: 1.00-1.21), but Westergaard et al 40 could not replicate the findings of Takei et al even when they employed their methods and concluded that there was no association between schizophrenia risk and influenza prevalence during any month of prenatal life.…”
Section: Studies Not Related To 1957 Pandemicmentioning
confidence: 95%
See 1 more Smart Citation
“…A larger study by Adams et al, 8 which included the birth cohort studied by Barr et al, found no such association. Takei et al 39 found an increased risk for subjects exposed 4 months prior to birth (RR = 1.12, 95% CI: 1.00-1.21), but Westergaard et al 40 could not replicate the findings of Takei et al even when they employed their methods and concluded that there was no association between schizophrenia risk and influenza prevalence during any month of prenatal life.…”
Section: Studies Not Related To 1957 Pandemicmentioning
confidence: 95%
“…18 Finally, 4 studies examined the relationship between the prevalence of influenza and the risk of schizophrenia in Denmark. 8,[38][39][40] Each study used a different method and covered a different birth period (1911-1950, 1911-1965, 1915-1970, and 1950-1984, respectively). Barr et al 38 reported an association between schizophrenia risk and relatively high levels of influenza exposure for the season during the sixth month of gestation but did not mention a RR.…”
Section: Studies Not Related To 1957 Pandemicmentioning
confidence: 99%
“…Only parents whose children were over the age of 15 years at the termination of follow-up on 31 December 1997 were included since less than 1.5% of schizophrenia cases develop before that age (Westergaard et al, 1999). The CPR was established in 1968 and all residents of Denmark were assigned a unique identification number that permits accurate linkage between registries.…”
Section: Methodsmentioning
confidence: 99%
“…Beginning in the 1980s, most studies [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25] used an ecological design and estimated the timing of the exposure to infectious agents in populations by obtaining retrospective data on epidemics from registries. Some studies [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41] additionally collected exposure data by interviewing mothers during or shortly after pregnancy or using their medical records.…”
Section: Introductionmentioning
confidence: 99%